Kajian Aktivitas Penambangan Minyak Tua dan Pertanian dalam Upaya Pengembangan Ekonomi Lokal Desa Bangowan Kecamatan Jiken Kabupaten Blora - Sigit Irvan Prasetyo (Department of Urban and Regional Planning, Diponegoro University, 2014)
Local Economic Development (LED) that aims to create new jobs in order to stimulate increased economic activity and improve local people's income. Desa Bangowan Kecamatan Jiken has two local potential that is agriculture and mining potential. The isues in Desa Bangowan include how much Local Economic Development activities by using natural resources, to providing new jobs and increase income, productivity and welfare of community. The purpose of study is to assess the productivity of labor and social welfare Desa Bangowan as miners and farmers to support local economic development. The method used is a quantitative method supported by qualitative method with descriptive statistical analysis and multiple regression analysis. Success indicator LED is not achieving that is, no empowerment of micro and small institution; PEL partnership is less perfect; unavailability of business cluster facilities; not occur multiplier effect on society; no efforts for the development of human resources. The conclusion is miners characteristics, miners labor productivity, welfare miners are better than farmers, economy of miners is known increasing.